2005
DOI: 10.1002/ccd.20471
|View full text |Cite
|
Sign up to set email alerts
|

Large tube section is the key to successful coronary thrombus aspiration: Findings of a standardized bench test

Abstract: Thrombus removal by aspiration is one of the adjunctive techniques used to avoid embolization during PCI for acute myocardial infarction. Numerous devices are now available, but little is known about the mechanical rationale used in comparing them. The aim of the present study was to determine parameters to obtain optimal thrombus aspiration (TA). Heparin- and antiplatelet-free blood samples were aspirated into 3 mm diameter standardized glass tubes to create a 30 mm long thrombus. Thrombus formation took plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Indeed, such a tip is unlikely to be completely immersed within the thrombus and thus would preferentially aspirate blood instead of thrombus. In agreement with our findings, Rioufol and colleagues (19) recently found that to achieve a complete thrombus aspiration, a beveled tip requires a higher degree of vacuum than an unbeveled one (200 vs. 150 mbars).…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, such a tip is unlikely to be completely immersed within the thrombus and thus would preferentially aspirate blood instead of thrombus. In agreement with our findings, Rioufol and colleagues (19) recently found that to achieve a complete thrombus aspiration, a beveled tip requires a higher degree of vacuum than an unbeveled one (200 vs. 150 mbars).…”
Section: Discussionsupporting
confidence: 93%
“…There is evidence that a larger aspiration catheter tip surface area leads to an increase in aspiration power at the tip, an effect that has been postulated to be responsible for a higher first pass efficacy in cardiac thrombectomy. 22 23 However, there is some debate concerning the impact of larger bore catheters on outcomes. 24 In acute ischemic stroke, mechanical thrombectomy performed with the ACE68 catheters also demonstrated higher first pass efficacy compared with the early generation ACE60 and ACE64 catheters.…”
Section: Discussionmentioning
confidence: 99%
“…Third, this large caliber equipment may result in access site complication and vessel wall injury of SMA and abdominal aorta. Recently, with the advancement of interventional technology, rapid‐exchange and low‐profile aspiration devices to have the ability to aspirate troublesome thrombus, crossability and flexibility have developed even for more small and tortuous coronary artery [8–10]. No previous report, however, has addressed the potential ability of this sort of aspiration device for SMA thrombo‐embolism.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of direct aspiration has already been reported in various vascular thrombo‐embolic lesions since Greenfield et al reported the successful endovascular aspiration therapy [2–7]. Recently, the direct aspiration using rapid‐exchange and low‐profile aspiration device has been applied to complex thrombus in coronary artery, smaller and more tortuous vessel in the whole body [8–10]. We describe the utility of direct aspiration using this sort of aspiration device for failed thrombolysis of acute thrombo‐embolic occlusion of the SMA.…”
Section: Introductionmentioning
confidence: 95%